Education to Increase Knowledge and Awareness of Household Fire Mitigation in Subdistrict of Lambung Bukit, Padang - Trisfa Augia; Hafizh Akramul Fikri; Aulia Putri Sudira; Catherine Natasya Ayunda; Zerifna Chairunnisa (Warta Pengabdian Andalas, 2025)
A fire is an uncontrolled event in which flames ignite an object or area, causing damage to the surrounding environment. In Indonesia, fire cases reach a significant number. Based on statistical data, the number of fires in Indonesia reached 5.336 cases in the period 2018 to 2023. The purpose of the service is to increase public knowledge and awareness of the importance of fire mitigation in households and provide appropriate solutions when a fire occurs. The service activity was held at the Kelurahan Lambung Bukit Office Hall, Pauh District, Padang City on Monday, December 2, 2024. The service method used is education through counseling and discussion, and is equipped with a pre-test and post-test to evaluate the level of knowledge of the participants. The average knowledge score of 17 participants before counseling was 51.76 and afterwards increased to 68.82. Based on the statistical test results of the average difference before and after counseling, a p-value of 0,000 was obtained, which stated that there was a significant increase in knowledge value. Through this service activity, an increase in knowledge and awareness of housewives and the general public regarding the importance of fire mitigation in the Lambung bukit settlement was obtained. It is recommended that policy makers undertake mitigation efforts against fires and form cadres from trained community elements to form Kelurahan that are prepared for fire disasters.